Dirāsah Tahlīliyah Limanhaj Tadrīs Altarākib Alnahwiyah Fī Kitāb Ta’lim Allughah Al’arabiyah Lilshafi Al awal Altsānawī Liwizārah Alsyu`ūn Aldīniyah Al Indūnīsiyah ām 2020 - Taufik Ismail; Abdul Halim Muhammad (Ukazh: Journal of Arabic Studies, 2022)
This research aims to discover the curriculum used in teaching grammatical structures in the book for teaching Arabic language for the first grade of high school of the Indonesian Ministry of Religious Affairs in 2020 and to know the advantages and shortcomings thereof. This research follows a descriptive and analytical approach, by following the curriculum of teaching grammatical structures in the textbook of teaching Arabic language for the first high grade of the Indonesian Ministry of Religious Affairs in 2020, then classifying it, presenting it, and concluding. The study proved that the textbook for teaching Arabic for the first secondary grade of the Indonesian Ministry of Religious Affairs in 2020 uses the curriculum for teaching grammatical structures, the inductive method and the standard method in explaining lessons, uses intermediate language in presenting lessons and controls movements in all words, and it proved the existence of advantages and shortcomings in it. Penelitian ini bertujuan untuk mengetahui kurikulum yang digunakan dalam pembelajaran struktur tata bahasa pada buku pengajaran bahasa Arab untuk kelas I Sekolah Menengah Atas Kementerian Agama Republik Indonesia Tahun 2020 dan untuk mengetahui kelebihan dan kekurangannya. Penelitian ini menggunakan pendekatan deskriptif dan analitik, dengan mengikuti kurikulum pembelajaran struktur gramatikal dalam buku teks pembelajaran bahasa Arab untuk kelas I Kementerian Agama Republik Indonesia Tahun 2020, kemudian mengklasifikasikannya, menyajikannya, dan menyimpulkannya. Hasil penelitian membuktikan bahwa buku ajar pengajaran bahasa Arab kelas satu Menengah Atas Kementerian Agama Republik Indonesia tahun 2020 menggunakan kurikulum untuk pengajaran struktur tata bahasa, metode induktif dan metode standar dalam menjelaskan pelajaran, menggunakan bahasa perantara dalam penyajian pelajaran dan harakat (tanda baca) di semua kata. يهدف هذا البحث إلى اكتشاف المنهج المستخدم في تدريس التراكيب النحوية في كتاب تعليم اللغة العربية للصف الأول الثانوي لوزارة الشؤون الدينية الإندونيسية عام 2020 ومعرفة الزايا والنقصان فيها. إن هذا البحث يسلك منهج الوصفي التحليلي، وذلك بتتبع منهج تدريس التراكيب النحوية في كتاب تعليم اللغة العربية للصف الأول الثانوي لوزارة الشؤون الدينية الإندونيسية عام 2020، ثم تصنيفه وعرضه والاستنتاج. أثبتت الدراسة بأن كتاب تعليم اللغة العربية للصف الأول الثانوي لوزارة الشؤون الدينية الإندونيسية عام 2020 يستخدم في منهج تدريس التراكيب النحوية، الطريقة الاستقرائية والطريقة القياسية في بيان الدروس و يستخدم اللغة الوسيطة في عرض الدروس ويضبط الحركات في جميع الكلمات، وأثبتت بوجود المزايا والنقصان فيه